Penegakan Hukum Administrasi Terhadap Penerbitan Izin Lingkungan Kegiatan Budidaya Tanaman Perkebunan Pala Intercroop Kakao Di Kabupaten Seram Bagian Barat - Latekay, Marlon; Pietersz, Jemmy Jefry; Sedubun, Victor Juzuf (Faculty of Law, Universitas Pattimura, 2023)
Introduction: Issuance of environmental permits by the West Seram Regency Government without supervision has resulted in non-compliance with environmental permits which has resulted in environmental damage.Purposes of the Research: This writing aims to examine and analyze the Authority of the West Seram Regency Government in supervising the Decree of the West Seram Regent Number 525-456 of 2017 concerning Environmental Permits for the Cultivation of Nutmeg Intercroop Cocoa Plantations, to study and analyze what administrative sanctions can be given West Seram Regency Government regarding violations of environmental permits. Methods of the Research: Normative research method with the type of research is qualitative analysis. The problem approach used is the statute approach, the conceptual approach and the case approach. The sources of legal materials used are Primary legal materials, Secondary legal materials, and Tertiary legal materials and are used as a technique for collecting legal materials, then processing and analyzing legal materials through methods of interpretation, harmonization, systematic and legal discovery.Results of the Research: The results of the study show that the authority to issue environmental permits by the West Seram Regency Government can automatically become an obligation for the West Seram Regency Government as the issuer of environmental permits to supervise environmental permits issued by the West Seram Regency Government, administrative sanctions that can be imposed by the Government West Seram District to violators of environmental permits is, written warning, government coercion, freezing of environmental permits and revocation of environmental permits.